2021
DOI: 10.3389/fmed.2021.657957
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alkaline Phosphatase and Muscle Mass, Strength, or Physical Performance in Patients on Maintenance Hemodialysis

Abstract: Introduction: Alkaline phosphatase (ALP) is an indicator for checking liver or bone disorders, but recent studies have shown the possibility of an additive indicator beyond the simple mineral-bone status in dialysis patients. The aim of the study was to evaluate the ALP level and various indicators for malnutrition, physical performance, or hospitalization in patients on hemodialysis (HD).Methods: This study was an observational study (n = 84). We included all patients undergoing HD with the following criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Besides, ALP is a zinc-containing metalloenzyme ( 36 ), thus it can be used as a marker of zinc status in the body ( 37 ). Meanwhile, it is reported that greater activity of serum ALP is conducive to energy metabolism and muscle mass ( 38 ). Intriguingly, the ZnMet group showed a significantly higher abundance of ALP, indicating a higher status of zinc concentration and muscle mass in the ZnMet group, which is as per the results of growth performance and carcass traits.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ALP is a zinc-containing metalloenzyme ( 36 ), thus it can be used as a marker of zinc status in the body ( 37 ). Meanwhile, it is reported that greater activity of serum ALP is conducive to energy metabolism and muscle mass ( 38 ). Intriguingly, the ZnMet group showed a significantly higher abundance of ALP, indicating a higher status of zinc concentration and muscle mass in the ZnMet group, which is as per the results of growth performance and carcass traits.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation contributes to the development of frailty [28]. ALP (U/L) Liver function ALP could influence bone disorder, muscle mass, strength, and physical performance [29].…”
Section: Crp (Mg/l) Inflammationmentioning
confidence: 99%
“…Vascular stiffening and accelerated vascular calcification are common in CKD and are associated with increased serum total ALP activity and increased mortality [7,8]. Chronic inflammation and oxidative stress, which are features of protein energy wasting syndrome, induce vascular ALP and fibro-calcification in cardiovascular tissue [9], and clinical indicators of malnutrition are associated with increased circulating ALP [10]. The process of vascular calcification involves the transdifferentiation of vascular smooth muscle cells (VSMC) to an osteoblast-like phenotype with increased expression of BALP [11].…”
Section: Introductionmentioning
confidence: 99%